50.6k views
0 votes
To its equivalent value on the right. Some answer options on the right will not be used.

User Bwalshy
by
5.5k points

1 Answer

4 votes

For this type of question, we use the properties of fractions addition.

1.-


\begin{gathered} -(2)/(3)+(-(1)/(6))=-(2)/(3)-(1)/(6)=-(2)/(3)\cdot(2)/(2)-(1)/(6) \\ =-(4)/(6)-(1)/(6)=-(5)/(6) \\ -(2)/(3)+(-(1)/(6))=-(5)/(6) \end{gathered}

2.-


\begin{gathered} -(1)/(4)+(-(3)/(8))=-(1)/(4)-(3)/(8)=-(1)/(4)\cdot(2)/(2)-(3)/(8) \\ =-(2)/(8)-(3)/(8)=-(5)/(8) \\ -(1)/(4)+(-(3)/(8))=-(5)/(8) \end{gathered}

3.-


\begin{gathered} -(1)/(4)+(-(1)/(2))=-(1)/(4)-(1)/(2)=-(1)/(4)-(1)/(2)\cdot(2)/(2) \\ =-(1)/(4)-(2)/(4)=-(3)/(4) \\ -(1)/(4)+(-(1)/(2))=-(3)/(4) \end{gathered}

User Kumpelka
by
5.6k points